The truth about forever - Dessen, Sarah (New York : Speak, 2004)
The summer following her father's death, Macy plans to work at the library and wait for her brainy boyfriend to return from camp, but instead she goes to work at a catering business where she makes new friends and finally faces her grief.
Angela Misa
Keywords: Grief -- Fiction; Death -- Fiction; Caterers and catering -- Fiction; Interpersonal relations -- Fiction